1978
DOI: 10.1002/1097-0142(197805)41:5<1746::aid-cncr2820410515>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Remineralization of enamel by a saliva substitute designed for use by irradiated patients

Abstract: A saliva substitute, VA-OraLube, was evaluated for ability to reharden dental enamel and to relieve intraoral soft tissue symptoms in patients receiving radiotherapy for malignancies of the head and neck. Treatments of 15, 30 and 60 minutes rehardened enamel by 3.1%, 4.0%, and 5.5%, respectively. In the second experiment, treatment for 60 minutes with the complete solution rehardened enamel by 5.2%. Omitting calcium, phosphorus and/or fluoride from the formulation greatly decreased this rehardening potential. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
4

Year Published

1983
1983
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 17 publications
1
18
0
4
Order By: Relevance
“…Experiments dealing with the remineralizing effects of saliva substitutes proved that the addition of low concentrations of fluoride (2-5 ppm) leads to a significant increase of microhardness on demineralized (and softened) enamel [30,31]. With the simultaneous addition of calcium and phosphate, the increase of microhardness was strongly pronounced [32], thus leading to the conclusion of an increased remineralization effect. Similar effects have been observed after the immersion of demineralized enamel samples in cow's milk [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments dealing with the remineralizing effects of saliva substitutes proved that the addition of low concentrations of fluoride (2-5 ppm) leads to a significant increase of microhardness on demineralized (and softened) enamel [30,31]. With the simultaneous addition of calcium and phosphate, the increase of microhardness was strongly pronounced [32], thus leading to the conclusion of an increased remineralization effect. Similar effects have been observed after the immersion of demineralized enamel samples in cow's milk [8].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, since patients with extensive mouth dryness are particularly susceptible to dental caries, it is desirable that artificial saliva is able to remineralize initial lesions in dental hard tissues. However, there is little information about any remineralizing effects of saliva substitutes or mouthwash solutions in the dental literature [9,[30][31][32]38]. Thus, the aim of this study was to analyze the effect of saliva substitutes on the mineral content of demineralized and sound enamel.…”
Section: Introductionmentioning
confidence: 99%
“…As salivary flow in patients after radiotherapy may be reduced drastically, it is obvious that repeated and prolonged application of saliva substitutes with low pH may promote enamel and dentin demineralization. This topic has been investigated in several in vitro studies, using substrata such as hydroxyapatite powder [20], bovine enamel [21], and dentin [22] as well as human enamel [23][24][25]. Although demineralizing effects after storage of tooth tissues in some artificial saliva solutions with low pH have been found [20,21], no definite correlation between tissue demineralization and saliva substitute pH could be established.…”
Section: Enamel and Dentin De-and Remineralizationmentioning
confidence: 99%
“…Moreover, artificial salivas should have a remineralising effect on dental hard tissues. 7 Previous studies showed a demineralising potential of linseed-based saliva substitutes on bovine dentin 8 , whereas mucin-based solutions revealed a neutral behaviour on enamel 9 and dentin 5,8,10 solubility, and were able to remineralise dental hard tissues in case of an adequate composition of calcium and phosphates as well as fluoride. 8,9,11 Commercially available saliva substitutes based on CMC (i.e.…”
Section: Introductionmentioning
confidence: 99%